2017
DOI: 10.7143/jhep.44.575
|View full text |Cite
|
Sign up to set email alerts
|

Usability of low-dose spiral computed tomography in the early detection of lung and mediastinal tumors

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…[ 7 ] In fact, our previous study demonstrated that CR did not contribute to the early detection of lung cancer at health checkups. [ 8 ] In addition, a recent randomized controlled trial on lung cancer screening by CR did not show a reduction in mortality compared with that following usual care. [ 9 ] This means that CR may not contribute to the early detection of lung cancer and may not be a useful modality for lung cancer screening.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] In fact, our previous study demonstrated that CR did not contribute to the early detection of lung cancer at health checkups. [ 8 ] In addition, a recent randomized controlled trial on lung cancer screening by CR did not show a reduction in mortality compared with that following usual care. [ 9 ] This means that CR may not contribute to the early detection of lung cancer and may not be a useful modality for lung cancer screening.…”
Section: Introductionmentioning
confidence: 99%